Konstitusionalitas Ketetapan Majelis Permusyawaratan Rakyat Dalam Hierarki Peraturan Perundang-undangan - Fajarwati, Meirina (UI Scholars Hub, 2018)
The Provision of the People Consultative Assembly is a kind and hierarchy of legislations in 2011 Law No. 12 on the Establisment of Law. The Provision of the People Consultative Assembly assignments again in hierarchy of legislation after being eliminated in the hierarchy of legislation with law number 10 years 2004 had created problems because that Provision can’t be judicial review by constitutional court or supreme court. The Provision of the people Consultative Assembly that can’t be judicial review has aroused problems related to exsistence of that Provision as stipulated in law number 12 years 2011